E-banking management: issues, solutions, and strategies - Shah, Mahmood,Clarke, Steve
E-banking management: issues, solutions, and strategies / Mahmood Shah, Steve Clarke .- Hershey, PA : :Information Science Reference , 2009 .- 299 p. ; 26 cm .- 9781605662527